Mobile personalized alzheimer’s disease model (PALM) for non-pharmacological therapy / Anis Hasliza Abu Hashim - Abu Hashim, Anis Hasliza (2021)
The growth of aging population is increasing rapidly together with the average of life expectancy and also contributed to aging-associated diseases. One of the common diseases among older people is Alzheimer’s disease. Alzheimer’s disease has no cure, and people who suffer from the disease have difficulties to remember and carry out daily activities. Computer technology has shown a possibility rehabilitative role in Non-pharmacological treatment for Alzheimer’s patients. However, the strategies and methods could be improved by having a platform that could assist people with Alzheimer’s disease in their therapy sessions. The main objective of this research is to propose a mobile personalized non-pharmacological therapy model that is used to enhance memory and stimulate cognitive function of Alzheimer’s disease patients. The first phase is to identify the issue of research area by using qualitative approach to understand the components used in personalized non-pharmacological therapies. The second phase aims to design and develop the proposed model, Personalized Alzheimer’s Disease Memory Book, that later will be used to construct a mobile personalized digital memory book application for Alzheimer’s disease. The third phase goal is to validate the proposed model with the experts. The design model was reviewed by 7 experts, with 4 experts in clinical and 3 experts in human computer interface. All of them have more than 10 years of experience in their fields. A design research methodology was adopted to ensure the successful of this research. It comprised of three phases; (i) problem formulation, (ii) design and develop, and (iii) evaluation. The instrument for model evaluation was constructed and distributed during semi-interview sessions with the experts. Two sets of questionnaires were involved, one set is for clinical experts and the other is for human computer interface experts. Usefulness and functionality were the areas being evaluated and validated by the experts to put forward the conclusions. Descriptive analyses, thematic analysis and Kappa coefficient methods were utilized in the analysis process. The findings in descriptive analysis revealed high agreement on the usability, functionality, approach as well as concept of the model and the application to assist Alzheimer’s disease patients to improve their memory and strengthen their cognitive function. This study has shown that the model is able to help enhancing patient’s wellbeing as well as encourage social interaction and communication with caretakers and family members. Experts believe that Personalized Alzheimer’s Disease Memory Book model and personalized digital memory book application for Alzheimer’s disease are the practical contributions to the body of knowledge. Besides that, the development of the application in this study has added to the increasing number of mobile application for Alzheimer’s disease that can be used in therapy session.